Association of protein disulfide isomerase family A, member 4, and inflammation in people living with HIV. (January 2023) - Wang, Ning-Chi; Chen, Hsuan-Wei; Lin, Te-Yu
Highlights: Plasma protein disulfide isomerase family A member 4 (PDIA4) levels in people living with HIV were higher than those in the healthy controls. Plasma PDIA4 levels reduced significantly after combination antiretroviral therapy. Plasma PDIA4 levels correlated with a decreasing trend in the HIV viral load. Plasma PDIA4 levels are closely associated with inflammation in people living with HIV. Abstract: Objectives: : Protein disulfide isomerase (PDI) family members are specific endoplasmic reticulum proteins associated with inflammation, obesity, and cancer. In HIV infection, the role of PDI family A, member 4 (PDIA4), is unclear. This study aimed to clarify the association between plasma PDIA4 levels and inflammation in people living with HIV (PLWH). Methods: : In this study, 287 PLWH and 74 healthy participants were enrolled. The plasma PDIA4 values, demographic data, laboratory data, and other inflammatory markers were recorded. The association between PDIA4 level and inflammatory extent was analyzed using logistic regression and Spearman rank-order correlations. Other results were analyzed using Student's t -test or chi-square test. Results: : In PLWH, the PDIA4 levels were positively associated with the inflammatory markers, interleukin 6 (r = 0.209, p = 0.001), and tumor necrosis factor-α (r = 0.162, p = 0.01) levels, but not with high-sensitivity C-reactive protein levels. Moreover, the plasma PDIA4 level of PLWH decreased after anti-viral treatment (p = 0.0001). Conclusion: : Plasma PDIA4 levels are closely associated with inflammation in PLWH and have a positive correlation with the viral load during anti-viral therapy. GRaphical Abstract: Image, graphical abstract